Financial Distress Prediction; Springate, Zmijewski, and GroverMethod - Anandha Sartika Putri; Rico Elhando Badri; Edi Pranyoto; Susanti Susanti; Winda Rika Lestari (Proceeding International Conference on Information Technology and Business, 2020)
The purpose of this study was to investigate the recommended method for predicting financial distress. There were 3 methods was used in this study, namely the Springate method, the Zmijewski method, and the Grover method. This study focused on the goods and consumer industrial sector companies listed on the IDX during the 2014-2018 period. The result of this study found that the Springate method had the highest level of sensitivity in predicting financial distress. In addition, this study also found that the Zmijewski method had the greatest accuracy and the smallest error level compared to other methodsKeywords: Financial Distress Method, Springate Method, Zmijewski Method, Grover Method